Phase difference measurements through means of digital sampling - Yeo, Qian. (2012)
This report provides a technical details of the student's Final Year Project being attached to A*STAR National Metrology Centre, working on the topic on “Phase difference measurements through means of digital sampling.” Software using Labview is to be developed to measure the phase difference of 2 voltage signals in order to calibrate a phase standard device at the electrical laboratory at National Metrology Centre. A couple of methods are being proposed by the student to measure phase difference of the 2 voltage signals and eventually, the degree of accuracy of each respective method is to be compared and analysed.